Sertoli and Germ Cells Within Atrophic Seminiferous Tubules of Men With Non-Obstructive Azoospermia - Jensen, Christian Fuglesang Skjødt; Wang, Danyang; Mamsen, Linn Salto; Giwercman, Aleksander; Jørgensen, Niels; Fode, Mikkel; Ohl, Dana; Dong, Lihua; Hildorf, Simone Engmann; Pors, Susanne Elisabeth; Fedder, Jens; Ntemou, Elissavet; et al. (Frontiers in Endocrinology, 2022)
Background: Infertile men with non-obstructive azoospermia (NOA) have impaired spermatogenesis. Dilated and un-dilated atrophic seminiferous tubules are often present in the testes of these patients, with the highest likelihood of active spermatogenesis in the dilated tubules. Little is known about the un-dilated tubules, which in NOA patients constitute the majority. To advance therapeutic strategies for men with NOA who fail surgical sperm retrieval we aimed to characterize the spermatogonial stem cell microenvironment in atrophic un-dilated tubules. Methods: Testis biopsies approximately 3x3x3 mm3 were obtained from un-dilated areas from 34 patients. They were classified as hypospermatogenesis (HS) (n=5), maturation arrest (MA) (n=14), and Sertoli cell only (SCO) (n= 15). Testis samples from five fertile men were included as controls. Biopsies were used for histological analysis, RT-PCR analysis and immunofluorescence of germ and Sertoli cell markers. Results: Anti-Müllerian hormone mRNA and protein expression was increased in un-dilated tubules in all three NOA subtypes, compared to the control, showing an immature state of Sertoli cells (p<0.05). The GDNF mRNA expression was significantly increased in MA (P=0.0003). The BMP4 mRNA expression showed a significant increase in HS, MA, and SCO (P=0.02, P=0.0005, P=0.02, respectively). The thickness of the tubule wall was increased 2.2-fold in the SCO-NOA compared to the control (p<0.05). In germ cells, we found the DEAD-box helicase 4 (DDX4) and melanoma-associated antigen A4 (MAGE-A4) mRNA and protein expression reduced in NOA (MAGE-A: 46% decrease in HS, 53% decrease in MA, absent in SCO). In HS-NOA, the number of androgen receptor positive Sertoli cells was reduced 30% with a similar pattern in mRNA expression. The H2AX expression was increased in SCO as compared to HS and MA. However, none of these differences reached statistical significance probably due to low number of samples. Conclusions: Sertoli cells were shown to be immature in un-dilated tubules of three NOA subtypes. The increased DNA damage in Sertoli cells and thicker tubule wall in SCO suggested a different mechanism for the absence of spermatogenesis from SCO to HS and MA. These results expand insight into the differences in un-dilated tubules from the different types of NOA patients.